3 in one Khalid Yasin lectures - Yasin, Khalid; One Islam Publications (N.S.W, Australia : One Islam Publications, 2005)
Contains 9 lectures by Khalid Yasin, compact in 3 discs, 3 lectures each discs
Vol. 1. Love and loyalty for Allah and His messenger. Islam and the media. Character of a muslim -- Vol. 2. Brotherhood in Islam. Islam and the modern world. The enemy within -- Vol. 3. Islam: the treasure uncovered. Why man should recognize God. Private session
Title from container
Lecturer : Khalid YAsin
Keywords: Islam -- Customs and practices; Religious life -- Islam; Islam in mass media